Endemic Methicillin-Resistant Staphylococcus Aureus: Nurses' Risk Perceptions and Attitudes - Pedro, AL (2014)
Dissemination of methicillin-resistant Staphylococcus aureus (MRSA) remains one of the most difficult challenges for prevention, control, and treatment of health care-associated infections. A survey and interviews were conducted on nurses from a hospital center. We found that most nurses' perceived risk of acquiring MRSA related to themselves (72%), other nurses (88.5%), and patients (97.8%). This perception influences attitudes, leading to compliance with the existing recommendations.